The Implementation Of Direct Practice Technique With Native Speakers In Teaching English At G-Land Bobby’s Surf Camp Banyuwangi - Ridwan; Maulana Ilmi, Rizqi; Adam, M. Alvin (Program Studi Akuntansi IKOPIN, 2025)
The objective of this research is to outline the application of the direct method in English Language Teaching (ELT) within the tourism department of Lembaga Kursus dan Pelatihan (LKP) Aloha Tegaldlimo, in collaboration with a native speaker from G-Land Bobby's Surf Camp in Banyuwangi. This study employs a descriptive qualitative research design to collect data, involving observations, interviews, and documentation by the researchers. The analyzed data indicated that there was improvement in students' speaking scores in ELT when interacting with native speakers. The findings of this research indicate that utilizing a direct method with native speakers is an excellent approach for developing speaking skills. Every student achieved success according to the success criteria score (SCS), Sure, please provide the text you'd like me to paraphrase. Based on the results, the researcher determined that the Direct Practice Method with native speakers in English Language Teaching for speaking skills effectively enhanced students' proficiency in introducing themselves to native speakers. The average speaking score is 88, indicating it is rated as excellent. The approach involves employing a direct practice method in English Language Teaching to enhance speaking skills. Subsequent steps included: initially, the teacher provided an introduction to native speakers to clarify the activity's purpose. Next, the educator outlines the phases of the learning activity model during a verbal introduction to native speakers. Third, the teacher provided an example introduction to the native speaker. In the fourth step, the instructor separates the students into pairs. The fifth one. Gathering introductory information for native speakers for students as requested by the teacher. On the sixth, the teacher guided the students to develop a strong, effective introduction to the native speaker along with the native speaker. The seventh one. Students crafted a strong, effective introduction, and the action was completed. The eighth one. The teacher provides positive feedback and many applauses to motivate students and show enthusiasm in participating in speaking introductions to native speakers. The teacher assessed the action on the ninth.